2018
DOI: 10.2460/ajvr.79.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic yield of dental radiography and cone-beam computed tomography for the identification of anatomic landmarks in small to medium-sized brachycephalic dogs

Abstract: OBJECTIVE To evaluate the diagnostic yield of dental radiography (Rad method) and 3 cone-beam CT (CBCT) methods for the identification of predefined anatomic landmarks in brachycephalic dogs. ANIMALS 19 client-owned brachycephalic dogs admitted for evaluation and treatment of dental disease. PROCEDURES 26 predefined anatomic landmarks were evaluated separately by use of the RAD method and 3 CBCT software modules (serial CBCT slices and custom cross sections, tridimensional rendering, and reconstructed panorami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…When evaluated together, the diagnostic yield of the 3 CBCT imaging modalities for the evaluation of non-dentoalveolar anatomic structures, such as canals and foramina, were superior to that of the DR method, except for the mandibular symphysis, which had comparable diagnostic yield between all imaging methods. This is consistent with previous studies in both veterinary (7, 13, 14) and human (4, 15, 16) dentistry that have shown that 3-D imaging is better suited to the identification and evaluation of anatomic structures than 2-D imaging such as dental radiography. The results of these studies, which showed that cephalometric evaluation of 2-D imaging often renders both inaccurate and imprecise measurements in comparison to 3-D imaging, encourage the exploration of potential further applications of CBCT in veterinary dentistry.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When evaluated together, the diagnostic yield of the 3 CBCT imaging modalities for the evaluation of non-dentoalveolar anatomic structures, such as canals and foramina, were superior to that of the DR method, except for the mandibular symphysis, which had comparable diagnostic yield between all imaging methods. This is consistent with previous studies in both veterinary (7, 13, 14) and human (4, 15, 16) dentistry that have shown that 3-D imaging is better suited to the identification and evaluation of anatomic structures than 2-D imaging such as dental radiography. The results of these studies, which showed that cephalometric evaluation of 2-D imaging often renders both inaccurate and imprecise measurements in comparison to 3-D imaging, encourage the exploration of potential further applications of CBCT in veterinary dentistry.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, a single panoramic view was found to be unsuitable for evaluation of the entire skull of the cat due to the inability to include all anatomic structures of interest in a single curved plane without superimposition of anatomic structures. This finding was similar to that of a previous study that evaluated the panoramic method for use in evaluating the identification of anatomic structures in brachycephalic dogs (7). However, the use of multiple reconstructed panoramic views for evaluation of anatomic landmarks in cats allowed for true parallel imaging and for the elimination of overlapping structures.…”
Section: Discussionsupporting
confidence: 90%
“…New anatomical abnormalities, such as macroglossia, that may contribute to obstruction are being discovered in the brachycephalic breeds 1 5. Brachycephalic breeds are known to be predisposed to malformations of the dental arch 6 7. This case report describes the contribution of dental malformation to the nasal obstruction in a pug.…”
Section: Introductionmentioning
confidence: 93%
“…Although intraoral radiographs are widely used to assess the dentoalveolar complex in veterinary patients, distortion and superimposition of dental structures and surrounding tissues are associated with this diagnostic imaging technique's bidimensional nature. CT and CBCT have been used in human and veterinary dentistry to evaluate the maxillofacial and dentoalveolar structures, where intraoral radiography has proven insufficient (10)(11)(12)(13)(14). Tomography imaging multiplanar reconstruction (MPR) and 3-D rendering provide the clinician superior visualization of anatomical structures and pathology without the superimposition of surrounded structures (10,(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%